Coronary flow reserve and oesophageal dysfunction in syndrome X. Issue 844 (February 1996) - Chauhan, A.; Mullins, P. A.; Gill, R.; Taylor, G.; Petch, M. C.; Schofield, P. M.
Abstract : The relative prevalence of abnormalities of coronary flow reserve and oesophageal function was ascertained in 32 syndrome X patients with typical angina chest pain, a positive exercise test, and normal coronary arteries. Coronary flow reserve in response to a hyperaemic dose of papaverine was measured using an intracoronary Doppler catheter positioned in the left anterior descending coronary artery. An abnormal coronary flow reserve was defined as being < 3.0. Patients were investigated for oesophageal dysfunction by manometry and 24-hour pH monitoring. Thirteen patients had an impaired coronary flow reserve (group 1) and 19 patients had a normal flow reserve (group 2). Eight of the 13 group 1 patients (62%) and 13 of the 19 group 2 patients (68%, p = NS) had evidence of oesophageal dysfunction on either manometry or pH studies. Therefore, a total of 26 (81%) syndrome X patients had either an abnormality of coronary flow reserve or oesophageal dysfunction suggesting that chest pain in these patients may be due to myocardial ischaemia or oesophageal dysfunction, thus confirming the heterogeneous nature of this syndrome. The prevalence of oesophageal abnormalities was independent of any abnormalities of coronary flow reserve.